Role of national and international organizations in shaping abortion laws and reproductive rights: A comparative legal and human rights perspective (Journal of Advances and Scholarly Researches in Allied Education, 2025)
All throughout the globe, discussions on human rights and the legality around abortion continue to be hotly contested. Policies pertaining to abortion, healthcare accessibility, legislative changes, and the preservation of reproductive rights are significantly influenced by national and international groups. Public health programs, lobbying in the courts, policy suggestions, awareness drives, research, and participation in international conventions on reproductive healthcare and women's rights are all ways in which these groups help. A multitude of Indian organisations, including the Ministry of Health and Family Welfare, the National Commission for Women, the United Nations Commission on Human Rights, and others, have endeavoured to enhance the availability of safe abortion services and reproductive healthcare. International human rights organisations, the UN, the UN Population Fund, and the World Health Organization are among the worldwide institutions that have fought for safe abortion as a matter of reproductive rights and health for women. This article examines the role of national and international organisations in shaping policy concerning abortion, healthcare access, reproductive justice, and other related issues. The report emphasises the need of improved institutional collaboration to guarantee that abortion services are accessible, legal, and safe across the world, as well as the difficulties in implementing reproductive healthcare rights.